Energy management of a thermally coupled fuel cell system and metal hydride tank. (18th October 2019) - Chabane, D.; Ibrahim, M.; Harel, F.; Djerdir, A.; Candusso, D.; Elkedim, O.
Abstract: Being produced from renewable energy, hydrogen is one of the most efficient energy carriers of the future. Using metal alloys, hydrogen can be stored and transported at a low cost, in a safe and effective manner. However, most metals react with hydrogen to form a compound called metal hydride (MH). This reaction is an exothermic process, and as a result releases heat. With sufficient heat supply, hydrogen can be released from the as-formed metal hydride. In this work, we propose an integrated power system of a proton exchange membrane fuel cell (PEMFC) together with a hydride tank designed for vehicle use. We investigate different aspects for developing metal hydride tanks and their integration in the PEMFC, using water as the thermal fluid and a FeTi intermetallic compound as the hydrogen storage material. Ground truth simulations show that the annular metal hydride tank meets the hydrogen requirements of the fuel cell, but to the detriment of the operating temperature of the fuel cell (FC). Highlights: We study the thermal coupling potential of PEMFC with metal hydride tanks. We develop a numerical model for heat and mass transfer in the system. We study the energy balance between the PEMFC and the storage system.